AN ANALYSIS OF MELINDA’S STRUGGLE IN SELF-EXPRESSION DURING TRAUMATIC CONDITION IN “SPEAK” MOVIE - Budiarto Budiarto; Nurul Lia Ahmadi; Suhendar Suhendar; Mangantar Sitohang (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2022)
In this research, the researcher analysis a movie entitled Speak. This movie tells about a young girl who suffered from traumatic experiences during her adolescence because of being rape victim. As a result, she can’t express herself and can’t communication with others comfortably. The aims of this research are to analyze and to explain the trauma that face by the main character, and her struggle to recover with it. The researcher uses the theory of Post-traumatic Stress Disorder, self-expression, and art therapy to analyze this research. This analysis shows that the main character of this movie is in a bad condition that is reflected to her daily activities. She suffers from guilt, shame, depression, losing concentrate and self-confidence. But finally, she can find the way to heal from her trauma through art class and speak the truth to the people.